Estudo comparativo de citocinas anti-inflamatórias em células tronco mesenquimais cultivadas com Cordia ecalyculata e biocurativo - Vieira, Henrique de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: In front of the medical finding that many patients can't earn total benefit of multifactor a etiology chronicle venous sorenesses using conventional treatments, relate door not with phitotherapy, the Biotechnology Department of the Botucatu blood center stablished, since 2003, a protocol of bioactive healing production that interface with the sore and stimulate the recover of the damaged area by the introduction of stem cells, commissioned from the skin by growing factors. Using the Tissue Engineering, that consists, in the organ and tissues regeneration, obtained by collection pieces of organs or tissues of the subject, that, dissociated in cells, are cultivated on scaffolds. The Cordia ecalyculata, known as porangaba, belongs to the boraginaceas Family, is a a plant, which the active ingredient is the allantoin, that has the anti-inflamatory capacity helping the cell proliferation, boosting the damaged skin recover and epitelization. By the popular knowledge of this phytotherapic, it proposes to study the evaluation of the anti-inflamatory action of the plant extracts in scaffolds by the liberation of pro cytokines and anti-inflamatory. Objectives: 1) compare the apoptosis index and the cell feasibility in mesenchymal stem cell culture. 2) Quantify the anti-inflamatory citokines level liberated in mensenchymal stem cell culture isolated in fat tissue in the presence of fibrin glue, platelet gel, and doped chitosan by the action of Cordia ecalyculata. 3) Develop a anti-inflamatory citokynes bank. 4) Define the best cell culture conditions to obtain big concentrations of anti-inflamatory citokynes. Material and Method: it was collected fragment of distinct patients in which the tissue was rigorously submited to the asepsis protocol, mechanical dissociation, isolation, CTM-TA cell culture. The cells were cultivated until the needed number to the studies using the Cordia, in which is known expresses the surfaces markers ...

Introdução: Diante da constatação clínica de que muitos pacientes não conseguem benefício completo da remissão de ulcerações crônicas venosas de etiologia multifatorial utilizando tratamentos convencionais associados ou não à Fitoterapia, o Setor de Biotecnologia do Hemocentro de Botucatu estabeleceu desde 2003, um protocolo de produção de curativos bioativos, que interagem com a lesão e estimulam a recuperação da área danificada por indução das células-tronco comissionadas da pele via fatores de crescimento. Através da utilização da Engenharia de Tecidos que consiste na regeneração de órgãos e tecidos, obtidos através da coleta de partes de órgãos ou tecidos do indivíduo, que, dissociados em células, são cultivadas sobre arcabouços ou suportes sintéticos (scaffolds). A Cordia ecalyculata, conhecida como porangaba, é da família das boraginaceas, é um arbusto cujo principio ativo é a alantoína que possui capacidade anti-inflamatória favorecendo a proliferação celular, acelerando a regeneração da pele lesada, epitelização e a proliferação de novas células. Através do conhecimento popular deste fitoterápico propõe-se para estudo a avaliação da ação anti-inflamatória dos extratos da planta em arcabouços (scaffolds) através da liberação de citocinas pro e anti-inflamatórias. Objetivos: 1) Comparar os índices de apoptose e viabilidade celular em cultura de células-tronco mesenquimais (CTMs) 2) quantificar os níveis de citocinas anti-inflamatórias liberadas em culturas de células-tronco mesenquimais isoladas de tecido adiposo na presença de cola de fibrina, gel de plaquetas, quitosana dopada sob a ação de Cordia ecalyculata. 3) Criar um banco de citocinas anti-inflamatória e 4) Definir as melhores condições de cultura celular para se obter elevadas concentrações de citocinas anti-inflamatórias; Material e Método: foi coletado fragmento de pacientes distintos nos quais o...
Keywords: Células-tronco; Plantas medicinais; Boraginaceas; Agentes anti-inflamatorios; Citocinas; Curativos biológicos; Stem cells; Cytokines